2019
DOI: 10.1080/13543776.2019.1629419
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrases as disease markers

Abstract: Introduction-The physiologic importance of fast CO 2 /HCO 3 interconversion in various tissues requires the presence of carbonic anhydrase (CA, EC 4.2.1.1). Fourteen CA isozymes are present in humans, all of them being used as biomarkers. Area covered-A great number of patents and articles were focused on the use of CA isozymes as biomarkers for various diseases and syndromes in the recent years, in an ascending trend over the last decade. The review highlights the most important studies related with each isoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 159 publications
1
56
0
Order By: Relevance
“…1 Several studies have pointed to the importance of the CAs and their inhibitors as an indicator for various diseases. [2][3][4][5][6] Of particular importance is the human isozyme CA1, which has been identified as a potential marker of various cancers (breast, oral, colorectal, lung, prostate), ankylosing spondylitis, diabetes, Sjogren's syndrome, and pancreatitis. [7][8][9][10][11][12][12][13][14][15][16][17][18][19][20][21] Also encouraging for early detection, the level of CA1 can be determined at point of care (POC) by its presence in easily obtained oral fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Several studies have pointed to the importance of the CAs and their inhibitors as an indicator for various diseases. [2][3][4][5][6] Of particular importance is the human isozyme CA1, which has been identified as a potential marker of various cancers (breast, oral, colorectal, lung, prostate), ankylosing spondylitis, diabetes, Sjogren's syndrome, and pancreatitis. [7][8][9][10][11][12][12][13][14][15][16][17][18][19][20][21] Also encouraging for early detection, the level of CA1 can be determined at point of care (POC) by its presence in easily obtained oral fluid.…”
Section: Introductionmentioning
confidence: 99%
“…22 Despite their promise, the current methods for detecting CAs are time consuming, expensive, require extensive clinical processing and expertise in analysis (ELISA, 2D PAGE, and mass spectrometry). 6 The lack of high sensitive, rapid, cheap, miniaturized, and user friendly diagnostics has restricted the utilization of CAs for research and clinical purposes.…”
Section: Introductionmentioning
confidence: 99%
“…CAs catalyze the fundamental reaction for life, which is the interconversion of water and carbon dioxide into dissociated ions of carbonic acid 12,13 . The 14 human isozymes of CAs are up-regulated and down-regulated from gene levels in diverse dysfunctions or diseases, which promotes CAs to be considered as disease biomarkers 14 . Representatively, CA9 is a uniformly induced gene as a reliable biomarker of hypoxia and worse prognosis in tumors, such as prostate and renal cancer 15,16 .…”
Section: Ivyspringmentioning
confidence: 99%
“…Carbonic anhydrase 9 (CA9), as a member of the carbonic anhydrase enzyme family, plays a pivotal role in stabilizing the extracellular pH value by catalyzing the reversible conversion of carbon dioxide into bicarbonate ions and protons and thus promoting intracellular proton carboxylation and excretion [5]. Previous studies have confirmed that the acidification of tumor microenvironment could promote tumor cell migration and invasion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased expression of CA9 has been suggested to be a poor prognostic factor in different types of cancer (e.g. breast, head and neck, stomach, liver, pancreas, colorectal carcinomas) [5]. To the best of our knowledge, there have not been any studies focusing on CA9 expression in SNSCC to date.…”
Section: Introductionmentioning
confidence: 99%